2016
DOI: 10.3138/jvme.0615-091r2
|View full text |Cite
|
Sign up to set email alerts
|

Career Preferences and Opinions on Animal Welfare and Ethics: A Survey of Veterinary Students in Australia and New Zealand

Abstract: Historically, the veterinary profession has understood animal welfare primarily in terms of animal health and productivity, with less recognition of animals' feelings and mental state. Veterinary students' career preferences and attitudes to animal welfare have been the focus of several international studies. As part of a survey in Australia and New Zealand, this study reports on whether veterinary students prioritize animal welfare topics or professional conduct on the first day of practice and examines links… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 20 publications
4
27
0
Order By: Relevance
“…How veterinary graduates handle these issues can have significant and detrimental effects on their wellbeing, as well as the health and welfare of animals and their owners. The results of the parent survey showed that as Australasian students progress through their training they increasingly express a preference to work in companion animal practice . Results from the current study suggested that students enrolled in veterinary schools in Australia and New Zealand focus on the AWE issues more closely related to their clinical responsibilities and how they can influence the health and wellbeing of individual patients and their owners.…”
Section: Discussionmentioning
confidence: 75%
See 4 more Smart Citations
“…How veterinary graduates handle these issues can have significant and detrimental effects on their wellbeing, as well as the health and welfare of animals and their owners. The results of the parent survey showed that as Australasian students progress through their training they increasingly express a preference to work in companion animal practice . Results from the current study suggested that students enrolled in veterinary schools in Australia and New Zealand focus on the AWE issues more closely related to their clinical responsibilities and how they can influence the health and wellbeing of individual patients and their owners.…”
Section: Discussionmentioning
confidence: 75%
“…The details of methodology used in this study and the full list of AWE topics chosen, as well as the results of the broader survey, are reported in a paper describing the parent survey . In brief, all students enrolled in veterinary undergraduate courses at universities in Australia and New Zealand during October 2014 were invited to participate in the survey.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations